Caracterização da fauna edáfica em fragmento florestal em áreas de cerrado - Souza, Ana Carolina Silva (2019)
The uniformity of distribution, increase or decrease of the edaphic arthropods indicate the sensitive changes that have taken place in the environments, with some specimens being considered good indicators of environmental quality. This work aimed to characterize the edaphic fauna and its relationship with abiotic variables in a forest fragment in the Cerrado Biome (MA). The research was carried out in the municipality of Chapadinha-MA. Sampling of edaphic fauna was carried out monthly during 2018, using pitfall traps. In each of the five study areas, 10 traps were placed in two transects (five per transect) arranged in parallel, totaling 50 samples per collection (month). The traps remained in the field for 24 hours, and after being collected, the material was washed and the specimens were stored. The sampled organisms were identified with the aid of an order-level stereoscope microscope. Kruskal- Wallis, Principal Component Analysis (PCA) and Tree regression analyzes were performed. 44,627 specimens of arthropods were collected, belonging to eight classes and 17 orders; the taxonomic categories with the largest populations were Hymenoptera (10 886), Acari (9 120), Diptera (6 156), Collembola (14 877), Blattodea (967), Coleoptera (951) and Araneae (633). The influence of abiotic variables on the composition and distribution of edaphic organisms was verified during the study period. The organisms were also influenced by the vegetation gradient in the five forest fragment areas. The secondary vegetation and swamp areas provided more favorable conditions for the high number of specimens to occur, contrasting with the limiting conditions offered in the other fragments (AP, AN, VsS). There was an absolute abundance of the Acari, Collembola and Hymenoptera groups, but each group of arthropods establishes different relationships with the variables.